Free thoracodorsal, perforator-scapular flap based on the angular artery (TDAP-Scap-aa): Clinical experiences and description of a novel technique for single flap reconstruction of extensive oromandibular defects. Issue 10 (October 2019) - Pau, Mauro; Wallner, Jürgen; Feichtinger, Matthias; Schwaiger, Michael; Egger, Jan; Cambiaso-Daniel, Janos; Winter, Raimund; Jakse, Norbert; Zemann, Wolfgang
Abstract: Purpose: The reconstruction of oromandibular defects can be challenging, particularly when considerable amounts of bone and soft tissues are lost. In such cases, the use of a single flap may be unsatisfactory and a concomitant free flap is needed. Here we present a chimeric, thoracodorsal perforator-scapular free flap based on the angular artery of the subscapular system (TDAP-Scap-aa) as an alternative technique for single flap reconstruction of extensive oromandibular defects. Materials and methods: The authors studied patients who underwent reconstructions of extensive oromandibular defects with a TDAP-Scap-aa free flap. The operative technique and the clinical experiences are described. Postoperatively, surgical complications were classified with the Clavien-Dindo Classification. Results: Five male patients (59.4 ± 8.8 years) were treated with the TDAP-Scap-aa. Average sizes for harvested hard and soft tissue components, which are both included in the flap and completely independently from each other, were 10.4 ± 1.5 cm of bone length, 2.6 ± 0.3 cm of bone height, 11.6 ± 4.8 cm of skin paddle length and 8.4 ± 1.7 cm of skin paddle width. The overall mean operation time (cut-suture) was 14.6 ± 0.9 h. The postoperative follow-up was 6 months. No complications requiring surgical treatment as well as donor site nerve damages were observed. Conclusions: In comparison to other double free flaps, the TDAP-Scap-aa offers several advantages such as higher amounts of hard and soft tissues without prolonged operation times, and provides satisfying aesthetic outcomes and little donor site morbidity due to the preservation of muscle and nerve structures. Therefore, the TDAP-Scap-aa constitutes a clinically reliable alternative in extensive oromandibular defect reconstruction.